The Nazi conspiracy : the secret plot to kill Roosevelt, Stalin, and Churchill [compact disc, unabridged] - Meltzer, Brad; Mensch, Josh (Macmillan Audio, 2023)
From the New York Times bestselling authors of The First Conspiracy and The Lincoln Conspiracy comes the little-known true story of a Nazi plot to kill FDR, Joseph Stalin, and Winston Churchill at the height of World War II.